2016
DOI: 10.1163/15691497-12341396
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Youth Violence in Socially Disadvantaged Neighborhoods in Nigeria

Abstract: Nigerian urban centers, especially the socially disadvantaged neighborhoods (sdns), like other disadvantaged communities across Africa, are increasingly becoming breeding grounds for youth violence and Armed Non-State Actors (ansas). The increasing waves of violence in socially disadvantaged communities in Nigeria and the inability of security apparatus to curtail them, suggests a ‘nation’ bewildered and a comatose state. This article attempts to dissect the root causes of youth violence in socially disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This finding resonates with broader literature emphasizing the multifaceted nature of crime dynamics and the need for holistic strategies (Oyelade, 2019). While education may influence employment opportunities, other dynamic factors such as economic conditions and market dynamics play pivotal roles in shaping the landscape of gainful employment (Abdullahi & Issah, 2016).…”
Section: Discussion Of Findingssupporting
confidence: 74%
See 2 more Smart Citations
“…This finding resonates with broader literature emphasizing the multifaceted nature of crime dynamics and the need for holistic strategies (Oyelade, 2019). While education may influence employment opportunities, other dynamic factors such as economic conditions and market dynamics play pivotal roles in shaping the landscape of gainful employment (Abdullahi & Issah, 2016).…”
Section: Discussion Of Findingssupporting
confidence: 74%
“…A more educated community or youth population demonstrates an increased tendency to refrain from committing crimes. This is because, despite the limited relationship between education and gainful employment, education opens up socio-economic opportunities (Achinulo, 2017;Ajide, 2019;Atakpo, 2020;Abdullahi & Issah, 2016;Ajide, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Socially disadvantaged neighborhoods (SDNs) are unplanned settlements usually populated by the less privileged individuals in the society. They are characterized by poor infrastructure, dilapidated and abandoned buildings, as a result of which they become breeding‐grounds for the commercialisation and consumption of illicit drugs (Abdullahi & Issah, 2016). A study by Handley et al (2015) found that neighborhood disadvantage was associated with more marijuana dependence symptoms among the adolescents.…”
Section: Resultsmentioning
confidence: 99%